GAMBARAN TINGKAT KEPUASAN PASIEN TERHADAP PERAWATAN ORTHODONTIK DI SMILEY DENTAL CARE PARIS VAN JAVA (Jurnal Kesehatan Siliwangi, 2020)
ABSTRACT Fixed orthodontic treatment is a treatment that aims to create a balance between the occlusal of the teeth, facial aesthetics and the stability of the treatment results. Measuring the success of service delivery is determined by the level of satisfaction of service recipients, in this case the patient. Quality of service and patient satisfaction are indicators of successful implementation of dental clinic services. Purpose Identified the level of patient satisfaction with orthodontic treatment at Smiley Dental Care. Method: This type of research used descriptive methods. The study population was patients who performed orthodontic treatment at Smiley Dental Care. Taken of sampling used total sampling, with more and less 30 respondents. Data was categorized as Likert scale data processing and data analysis was displayed in the form of frequency distribution. The results of research description of patient satisfaction with orthodontic treatment at Smiley Dental Care showed the level of satisfaction with the speed of service time with a percentage of 63.3% (19 people) was very satisfied. Satisfaction with service procedures with a percentage of 66.7% (20 people) was very satisfied. Patient satisfaction with the comfort of facilities and infrastructure with a percentage of 56.7% (17 people) was very satisfied. Conclusion: Description of the level of patient satisfaction with the quality of orthodontic care provided at Smiley Dental Care was very satisfied. Key words: Orthodontic treatment, patient satisfaction, Dental Clinic.